Pengaruh iklan dan strategi pemasaran terhadap minat beli konsumen - Hidayat, Mohamad Ahsin Maulana (Maliki Interdisciplinary Journal, 2023)
This article discusses the important impact of a company advertising and marketing strategy in a competitive era. By understanding the influence of advertising and marketing strategy, the company can deploy their marketing efforts more smartly and effective, and achieve better results. Advertising help the companiy introduce products or service to consumers who are target market, crate differences in a crowded market, and build emotional attachments with consumers. Advertising as the main element in marketing communication has a strategic role in shaping brand image, increasing product awareness, and influencing consumer buying interest. Well targeted and creative advertisement can build connections between brands and consumers, as well as trigger higher purchase interest, help companies respond to changing market trends, and maintain their competitiveness.